Do Central Banks Need Capital? - Stella, Peter (IMF Working Papers; Working Paper ;, 1997)
Central banks may operate perfectly well without capital as conventionally defined. A large negative net worth, however, is likely to compromise central bank independence and interfere with its ability to attain policy objectives. If society values an independent central bank capable of effectively implementing monetary policy, recapitalization may become essential. Proper accounting practice in determining central bank profit or loss and rules governing the transfer of the central bank's operating result to the treasury are also important. A variety of country-specific central bank practices are reviewed to support the argument.